Mars ejection times and neutron capture effects of the nakhlites Y000593 and Y000749, the olivine-phyric shergottite Y980459, and the lherzolite NWA1950 - Christen,Franziska; Eugster,Otto; Busemann,Henner (National Institute of Polar Research, 2005)
P(論文) We measured the concentrations and isotopic composition of the noble gases He, Ne, Ar, Kr, and Xe in the paired antarctic nakhlites Y000593 and Y000749, and in the antarctic olivine-phyric shergottite Y980459. Furthermore, we analyzed He, Ne, and Ar in lherzolite NWA1950. For the two nakhlite specimens we obtain Mars ejection times of 11.2±1.2Ma and 12.3±1.8Ma, respectively, in agreement with those for the four nakhlites dated before. Y980459 yields longer cosmic-ray exposure (CRE) ages based on ^(21)Ne and ^(38)Ar (2.9 and 2.5Ma, respectively) than based on ^3He, ^(81)Kr-^(83)Kr, and ^(10)Be (1.5, 1.9, and 1.1Ma, respectively).We interpret this difference to be due to an additional cosmogenic component produced by solar cosmic rays. The Mars ejection time of this meteorite is essentially its CRE age of 1.1Ma and agrees with the ejection times of the four other olivine-phyric shergottites. The ejection time of NWA1950 is 4.1±1.4Ma and lies within the range of the other three lherzolites. In the two nakhlites and in Y980459 we observe effects induced by the reaction ^(79)Br (n, γβ) ^(80)Kr. For the nakhlites this ^(80)Kr was produced in free space during Mars-Earth transfer; from its concentration we calculate a pre-atmospheric mass of >170kg. On the other hand, a pre-atmospheric size for the Y980459 meteoroid can not be derived from our data. We interpret the occurrence of an excess of ^(80)Kr_n to be due to trapping of this nuclide from the martian atmosphere, as was observed by other workers for martian meteorite EETA79001. For Y980459 we also find an excess of 71×10^(-8)cm^3STP ^(40)Ar/g that originates from trapped martian atmospheric gases. We show that up to eight impact events in a time span of 0.73Ma to 19.8Ma are responsible for ejecting the martian meteorites studied until now. Each event occurred in a specific surface region characterized by the mineralogy of the meteorites blasted off by these cratering processes. departmental bulletin paper